Academic Quality through Servant Leadership and Learning Satisfaction among Education Students - Giantama, Mohamad Shepna; Karnati, Neti; Rahmawati, Desi (Universitas Negeri Jakarta, 2025)
BackgroundDespite the growing body of research on leadership styles in educational contexts, limited scholarly attention has been devoted to examining how servant leadership specifically influences academic quality through the mediating role of learning satisfaction in teacher education faculties. PurposeThis study investigates the interplay between servant leadership, learning satisfaction, and academic quality among education students in higher education institutions. Design/method/approachEmploying a qualitative library research design, this study systematically reviews and synthesizes peer-reviewed journal articles, academic books, and policy documents published between 2019 and 2025. The research procedure involves comprehensive literature identification, thematic categorization, and iterative data analysis through reduction, classification, comparison, and synthesis. Source triangulation and cross-referencing of theoretical positions ensure the trustworthiness of findings. ResultsThe results reveal three principal themes: servant leadership fosters a supportive academic environment that enhances student engagement and motivation; learning satisfaction serves as a critical mediating mechanism linking leadership practices to academic outcomes; and the synergistic interaction between servant leadership and learning satisfaction produces a compounding positive effect on academic quality. This study proposes an integrative conceptual framework demonstrating the interconnected pathways through which servant leadership and learning satisfaction collectively shape academic quality. Contribution/valueThe findings contribute to educational management theory by addressing the identified research gap and offering practical implications for faculty leaders seeking to enhance academic quality in teacher education programs